PEMBENTUKAN PORTOFOLIO OPTIMAL UNTUK PENGEMBALIAN KEPUTUSAN INVESTASI MENGGUNAKAN INDEKS TUNGGAL PADA SAHAM JAKARTA ISLAMIC INDEKS DI BURSA EFEK INDONESIA - B41111037, Jumiana (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
The purpose of this research is to determine what stocks are formed in the optimal portfolio on the stocks which are included in Jakarta Islamic Index (JII) with a single index model and the proportion of the funds. In addition, the aim of this research is also to determine the risk level and JII stock portfolio restitutiom which was formed during the research. Analysis of the securities was done by comparing the excess return to beta (ERB) with its Cut Off Rate (Ci) of each stock. The stocks that have ERB more than Ci are used as candidate portfolio, while the stocks that have Ci more than ERB are not included in the portfolio. The samples are 37 stocks of Jakarta Islamic Index Company. The result shows that from 37 samples which are selected companies, there are 16 companies which make up the compotition of the optimal portfolio with the proportion of stock funds HRUM, ITMG, ENRG, and INTP 1%, CTRA 2%, MPPA 3%, BSDE 4%, PWON 5%, INDF, PTPP, PGAS, and WIKA 6%, JSMR 9%, ICBP 10%, UNVR 14%, and KBLF sebesar 25%. The portfolio that has performed produced 2,568% portfolio return and 1,533% portfolio risk. Keywords: Optimal portfolio, Single Index Model